منهج الشيخ محمد الطاهر بن عاشور في عرض أسماء السور القرآنية وتوجيهها من خلال سورة التحريرمن التنوير -من سورة الفاتحة الى سورة الكهف- - بكوش, فاطمة الزهراء (University Of Eloud جامعة الوادي, 2019)
"عنوان هذا البحث: منهج الشيخ محمد الطاهر بن عاشور في عرض أسماء السور القرآنية وتوجيهها، من خلال تفسيره التحرير والتنوير، والإشكال الرئيسي الذي تطرحه هذه الدراسة ،كالآتي: كيف لنا أن نتطلع لدلالات محتوى السور من خلال تسمياتها؟وكيف كان عرض الشيخ بن عاشور لهذا المبحث الجليل من علم السور القرآنية في تفسيره ؟ وللإجابة عليها قسمتُ العمل في البحث إلى شقين: الشق النظري: والذي كان في مبحثين تناولت فيهما التعريف بالإمام ابن عاشور رحمه الله وتفسيره، ودراسة أسماء السور القرآنية كمبحث من مباحث علوم القرآن، وتوضيح ذلك في خطة البحث. الشق التطبيقي: وفيه مبحثان درست من خلالهما إشكاليات الدراسة، التي كانت حول آراء الشيخ بن عاشور حول محاور تسميات السور القرآنية، ومنهجه في تدارس أسماء السور وكيفية عرضها. ومن النتائج الأساسية المتوصل إليها: أن أسماء السور تشكل إشارات محورية في الدلالة على أبرز محتوى في السورة، والذي يتبين من خلال توجيه التسمية. أن الإمام بن عاشور قد سلك مسلكا فريدا في إبداء آرائه حول الموضوع، وأجاد في منهجه وعرضه لأسماء السور منطلقا من الاستقراء للتسميات وتمحيص مضمونها ومظانها التي أكثر العزو لها، وبرؤيته النقدية الفاحصة في اختياره وترجيح مصادره. " "Title of this research: Methodology of Sheikh Mohammed Al-Taher bin Ashour in the presentation of the names of the Quranic Suras and guidance, - from Al-Fatihah to Al-Kahf as a model - through his interpretation of liberation and enlightenment, and the main forms presented by this: How do we look for the significance of the content of the fence through its labels? And how was the presentation of Sheikh Ben Ashour for this reason? And to answer them The theoretical part: which was in two subjects in which the definition of Imam Ibn Ashour, may Allah have mercy on him, and the interpretation of the names, and study the names of the Quranic suras as a researcher of the science of the Koran, and clarify that in the research plan. Applied part: which examined the problems of the study, which was about the views of Sheikh bin Ashour on the axes of the designations of the Quranic wall, and his approach to the study of the names of the fence and how to display, the most prominent choices from among its sources. Key findings include: Imam Bin Ashour has taken a unique course in expressing his views on the subject, and he mastered in his methodology and presentation of the names of the fence starting from the extrapolation of the nomenclature and scrutiny of the content and fluorescence, which is more attributed to them, and his critical view in his choice and weighting of his sources. "
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: منهج- السور القرآنية - التحرير والتنوير; Curriculum - Quranic Surahs - Liberation and Enlightenment